Women in print 2 : production, distribution and consumption - Archer-Parré, Caroline; Moog, Christine, 1969-; Hinks, John, 1946- (Oxford ; New York : Peter Lang, 2022)
"Women in Print 2 is a collection of essays in two related volumes which consider the diversity of roles occupied by women in the authorship, design, production, distribution and consumption of printed material from the fifteenth century onwards. The contributions included in Women in Print 2 cover the whole of the 'letterpress era' in Europe from the early fifteenth century to the mid-twentieth century. The essays address three themes: the role of women in the production of print; in its distribution; in addition to some neglected areas of women's consumption of print. To a greater extent the participation of women in the production and distribution of print has been written by the men who dominated the trade. Women in Print 2 explores the often-overlooked contribution to the business aspects of the printing and publishing industries, particularly female involvement in roles that were customarily seen as male preserves. This collection of essays brings together insights from multiple perspectives, seeking to recover the unheard voices and hitherto unnoticed activities of the many women who participated in the production, distribution and consumption of the printed word and image."-- (Provided by publisher.)
boek